2001
DOI: 10.1002/ana.1123
|View full text |Cite
|
Sign up to set email alerts
|

Transected neurites, apoptotic neurons, and reduced inflammation in cortical multiple sclerosis lesions

Abstract: Multiple Sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system that causes motor, sensory, and cognitive deficits. The present study characterized demyelinated lesions in the cerebral cortex of MS patients. One hundred twelve cortical lesions were identified in 110 tissue blocks from 50 MS patients. Three patterns of cortical demyelination were identified: Type I lesions were contiguous with subcortical white matter lesions; Type II lesions were small, confined to the cortex, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

56
1,214
5
30

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,316 publications
(1,305 citation statements)
references
References 43 publications
56
1,214
5
30
Order By: Relevance
“…Such evidence exists. Although not surrounded by oligodendrocytes, transected dendrites occur in both demyelinated and myelinated cortex 11. A recent study revealed a widespread and pronounced loss of dendritic spines in MS cortex independent of cortical demyelination and axon loss 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such evidence exists. Although not surrounded by oligodendrocytes, transected dendrites occur in both demyelinated and myelinated cortex 11. A recent study revealed a widespread and pronounced loss of dendritic spines in MS cortex independent of cortical demyelination and axon loss 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, cortical pathology seems to extend beyond the area of demyelinated lesions. Histological studies demonstrated transected neurites not only in axons within demyelinated lesions but also in dendrites within the myelinated cortex,11 and a recent study demonstrated loss of dendritic spines independent of cortical demyelination and axon loss 2…”
mentioning
confidence: 99%
“…In fact, GM atrophy has been found to be associated with changes in all cognitive domains in MS (Morgen et al., 2006). This is not surprising as several pathological (Kutzelnigg et al., 2005; Peterson, Bo, Mork, Chang, & Trapp, 2001) and MRI (Calabrese, Atzori, et al., 2007; Calabrese, De Stefano, et al., 2007; De Stefano et al., 2003) studies have shown that the cerebral cortex is profoundly affected in MS. Indeed, cortical atrophy has been proposed as one of the major underlying substrates of cognitive impairment in MS (Amato et al., 2004; Benedict et al., 2004; Tekok‐Kilic et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies have demonstrated the presence of gray matter (GM) lesions (Peterson et al, 2001;Geurts et al, 2005) and brain atrophy (Chard et al, 2002;Anderson et al, 2006). Total brain atrophy can be viewed as a surrogate marker of the destructive pathological processes taking place in MS and can be observed with magnetic resonance imaging (MRI) by measuring the brain parenchymal fraction, a normalized measure that represents the sum of both gray matter (GM) and WM atrophy (Chard et al, 2002).…”
Section: Introductionmentioning
confidence: 99%